"The Truest, the Best, and the Most Accurate [ճշմարտագոյնն լաւն եւ անսխալն]": Reading Color and Image in a Fifteenth-Century Armenian Manuscript from Kaffa - Qiu, Earnestine. (Tufts University. Tisch Library., 2019)
The illustrated fifteenth-century Armenian manuscript of The Lives of the Desert Fathers (MS 285, Armenian Patriarchate of Jerusalem) produced in Crimea belongs to a rich textual tradition. Despite its significance as an early and sumptuously illustrated copy of the Lives, however, Jerusalem 285 has received very little attention aside from one monograph published by Nira Stone in 1997. Stone focused on the political context and stylistic elements to explain the genesis and artistic choices of the manuscript. This paper instead uses the accompanying colophon written by the copyist and illustrator, Thaddeus Avraments', to understand the colors and images of Jerusalem 285. It places the visual and textual concerns of Thaddeus within the Armenian image making and viewing tradition, while also exploring further implications for understanding attitudes towards images in the greater medieval world.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Art and Art History.; Advisor: Christina Maranci.; Committee: Eva Hoffman, and David Proctor.; Keyword: Art history.